THE OBSTACLE IN TEACHING SPEAKING BY USING DEBATE TECHNIQUE - Sri Wahyuni; Hijjatul Qamariah; Sofyan Abdul Gani; Yunisrina Qismullah (Getsempena English Education Journal, 2018)
The study highlighted the obstacles of teaching Speaking using debate technique at higher education students atAbulyatama University under the course named Critical Speaking. The aim of this study was to identify the obstacles found in teaching speaking by using debate techniques in higher education. the study was designed using the descriptive qualitative method where the data was collected through interviewing the designated lecturer who taught the course and then analyzed through three basic steps, they are data condensation, data display,and data conclusion. The lecturer described her difficulties in teaching speaking using debate technique that related to the limitation of time, participation, critical thinking ability,and the speaking ability. Hence, the lecturer applied some solution to the challenges, such as obligating the case-building process even to the audiences, assigning the students to enhance their knowledge on the current issues and starting the debate by the very basic motion.